Soft package laminate and secondary battery
Patent Information
- Application Number
- CN202280040003.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-01
- Filing Date
- 2022-09-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-09-28
AI Technical Summary
然而,关于根据相关技术的软包膜叠层,当软包型二次电池处于恶劣的环境条件下时,软包的密封部可能漏气
[0029] According to related technologies, in order to improve adhesion to the gas barrier layer (which is a metal layer), when manufacturing a pouch film laminate, the first sealant layer attached to the gas barrier layer is typically made of a material with lower fluidity than the second sealant layer. However, in battery casings manufactured using pouch film laminates according to related technologies, the interface between the first and second sealant layers peels off when gas is generated inside the pouch or when external force is applied. Therefore, seal durability deteriorates.
Smart Images

Figure CN117426004B_ABST
Abstract
Description
Technical Field
[0001] Cross-reference to related applications
[0002] This application claims priority to Korean Patent Application No. 10-2021-0131121, filed on October 1, 2021, the entire contents of which are incorporated herein by reference. Technical Field
[0004] The present invention relates to a soft-pack film stack and a secondary battery manufactured by forming the soft-pack film stack, and more specifically, to a soft-pack film stack that enhances the sealing strength of the soft pack and a secondary battery manufactured by forming the soft-pack film stack. Background Technology
[0005] Generally, there are several types of rechargeable batteries, such as nickel-cadmium batteries, nickel-metal hydride batteries, lithium-ion batteries, and lithium-ion polymer batteries. These rechargeable batteries are used not only in small products such as digital cameras, P-DVDs, MP3 players, cellular phones, tablets, portable gaming devices, power tools, and electric bicycles, but also in large products requiring high power, such as electric vehicles, hybrid electric vehicles, and power storage devices or backup power storage devices for storing surplus electricity and new renewable energy.
[0006] To manufacture a secondary battery, firstly, an electrode active material slurry is coated onto the positive and negative current collectors to create the positive and negative electrodes, and then the positive and negative electrodes are stacked on both sides of a separator to form an electrode assembly with a predetermined shape. Subsequently, the electrode assembly is housed in a battery casing, and after the electrolyte is injected into the battery casing, the battery casing is sealed.
[0007] Secondary batteries are classified into pouch cells, can cells, etc., based on the material of the casing that houses the electrode components. In pouch cells, the electrode components are housed in a pouch made of a flexible polymer material. In can cells, the electrode components are housed in a casing made of materials such as metal or plastic.
[0008] A soft-pack battery casing is manufactured by forming a cup portion on a flexible soft-pack film laminate through a pressing process. When the cup portion is formed, the electrode assembly is housed within the internal receiving space of the cup portion, and a sealing portion is formed. This allows the manufacture of a secondary battery.
[0009] Typically, a pouch cell laminate comprises multiple layers, in which a polymer film, such as polyethylene terephthalate, is laminated on one surface of a metal gas barrier layer, and a sealant layer is laminated on the other surface. However, regarding pouch cell laminates according to related technologies, when the pouch-type secondary battery is subjected to harsh environmental conditions, the seal of the pouch may leak. Therefore, the electrode assemblies housed inside the pouch may become contaminated or malfunction. Summary of the Invention
[0010] Technical issues
[0011] The present invention provides a flexible film stack that improves the sealing strength of the flexible package by optimizing the yield strength of the sealant layer.
[0012] The purpose of this invention is not limited to the foregoing purposes, and other purposes not described herein will be clearly understood by those skilled in the art from the following description.
[0013] Technical solution
[0014] In the flexible film stack according to an embodiment of the present invention, a base layer, a gas barrier layer, and a sealant layer are stacked sequentially. The sealant layer includes a first sealant layer disposed adjacent to the gas barrier layer and a second sealant layer stacked on the first sealant layer, wherein ΔY according to Equation 1 is 66% to 120%.
[0015] [Equation 1]
[0016] ΔY = {(Yield strength of the second sealant layer - Yield strength of the first sealant layer) / Yield strength of the first sealant layer} × 100%
[0017] In the flexible film stack according to the present invention, the difference between the yield strength of the first sealant layer and the yield strength of the second sealant layer may be less than or equal to 8 N / 15 mm.
[0018] In the soft-film laminate according to the present invention, the yield strength of the first sealant layer may be less than the yield strength of the second sealant layer.
[0019] In the flexible film stack according to the present invention, the yield strength of the first sealant layer can be from 7 N / 15 mm to 15 N / 15 mm.
[0020] In the flexible film stack according to the present invention, the yield strength of the second sealant layer can be from 10 N / 15 mm to 30 N / 15 mm.
[0021] In the flexible film stack according to the present invention, the thickness ratio of the first sealant layer to the second sealant layer can be from 1:0.3 to 1:3.
[0022] In the flexible film stack according to the present invention, the thickness of the first sealant layer can be from 10 μm to 60 μm.
[0023] In the flexible film stack according to the present invention, the thickness of the second sealant layer can be from 20 μm to 70 μm.
[0024] In the flexible film stack according to the present invention, the first sealant layer and the second sealant layer may comprise polypropylene (PP), and the gas barrier layer may comprise aluminum (Al).
[0025] In the flexible film stack according to the present invention, the peel strength between the gas barrier layer and the first sealant layer can be greater than 23 N / 15 mm.
[0026] When two soft films are stacked in such a way that their respective second sealant layers are in contact with each other, and then sealed for 2 seconds at 180°C and 0.4MPa to form a seal, the breaking strength of the seal measured at 25°C can be greater than or equal to 100N / 15mm, and the breaking strength of the seal measured at 60°C can be greater than or equal to 80N / 15mm.
[0027] Additionally, according to another embodiment of the present invention, a secondary battery includes a pouch-type battery casing manufactured by forming any one of the pouch film stacks described above, and an electrode assembly housed inside the pouch-type battery casing.
[0028] Beneficial effects
[0029] According to related technologies, in order to improve adhesion to the gas barrier layer (which is a metal layer), when manufacturing a pouch film laminate, the first sealant layer attached to the gas barrier layer is typically made of a material with lower fluidity than the second sealant layer. However, in battery casings manufactured using pouch film laminates according to related technologies, the interface between the first and second sealant layers peels off when gas is generated inside the pouch or when external force is applied. Therefore, seal durability deteriorates.
[0030] In the flexible film laminate according to the invention, which addresses the aforementioned limitations, the difference in yield strength between the first sealant layer and the second sealant layer is controlled within a specific range. Therefore, peeling at the interface between the first and second sealant layers due to external forces or gas generation can be suppressed. Consequently, the sealing durability of the flexible package manufactured by sealing the flexible film laminate can be improved. Attached Figure Description
[0031] Figure 1 This is a cross-sectional view of the soft film stack according to the present invention.
[0032] Figure 2 This is a cross-sectional view showing the sealing portion of the soft-pack battery casing according to the present invention.
[0033] Figure 3 This is an exploded assembly diagram of the secondary battery according to the present invention.
[0034] Figure 4 The image shows the state under which the peel strength between the gas barrier layer and the sealant layer according to the present invention is being measured.
[0035] Figure 5 The image shows the state of measuring the fracture strength of a seal manufactured using a soft film laminate according to the present invention. Detailed Implementation
[0036] The advantages and features of the invention, and its implementation methods, will be illustrated by the following detailed description of embodiments in conjunction with the accompanying drawings. However, the invention can be embodied in various different forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art. Furthermore, the invention is defined only by the scope of the claims. Throughout this specification, the same reference numerals refer to the same elements.
[0037] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Furthermore, terms defined in general dictionaries are not to be ideally or excessively interpreted unless explicitly and specifically defined.
[0038] The terminology used in this specification is for illustrative purposes only and does not limit the invention. In this specification, the singular form includes the plural form as well as the singular form, unless the context clearly indicates otherwise. The meaning of "comprising" and / or "including" as used in this specification does not exclude the presence or addition of one or more components in addition to those mentioned.
[0039] Preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0040] Furthermore, when a component is described as "comprising" some elements, it should be understood that it may also include other elements unless explicitly stated otherwise.
[0041] In this specification, the top side of the drawing may be referred to as the "upper part" or "upper side" of the component illustrated in the drawing, and the lower side may be referred to as the "lower part" or "lower side." Additionally, the portion between the upper and lower parts of the component illustrated in the drawing, or the portion other than the upper and lower parts, may be referred to as the "side part" or "lateral side." These relative terms such as "upper part" or "upper side" are used to describe the relationship between the components illustrated in the drawing, and this disclosure is not limited by these terms.
[0042] In this specification, the direction toward the interior space of the structure may be referred to as "interior," and the direction protruding into the open exterior space may be referred to as "exterior." These relative terms such as "interior" or "exterior" may be used to describe the relationships between the components illustrated in the accompanying drawings, and this disclosure is not limited to these terms.
[0043] As used in this article, the expression "A and / or B" refers to A, B, or A and B.
[0044] In the specification, when a component is referred to as being connected to another component, it includes the case where the one component is directly connected to the other component, and also the case where the one component is connected to the other component and there is an intermediate element between them.
[0045] In this specification, yield strength is expressed as the ultimate stress at which elastic deformation occurs with a bias stress of 0.2%. This was measured using a measuring device, UTM (Zwick), at a speed of 50 mm / min while stretching a 15 mm × 80 mm polypropylene film sample in an environment of 25°C and 40% relative humidity.
[0046] In the specification, the breaking strength of the seal refers to the stress that causes the seal to break. Here, two soft film layers are stacked such that their respective second sealant layers are in contact with each other, and then sealed for 2 seconds at 180°C and 0.4 MPa to form a seal. Specifically, the breaking strength of the seal refers to the maximum tensile strength measured when the seal breaks. Here, the sample with the seal is cut into 15 mm wide pieces, and the ends of the vertically stacked soft film layers in the sample are fastened to the upper / lower clamps of the measuring device (UTM, Zwick) and then pulled vertically at a speed of 5 mm / min.
[0047] Soft film stack
[0048] The flexible film laminate according to the invention comprises a base layer, a gas barrier layer, and a sealant layer stacked sequentially. In this case, the sealant layer includes a first sealant layer arranged adjacent to the gas barrier layer and a second sealant layer stacked on the first sealant layer. Furthermore, ΔY according to Equation 1 is 66% to 120%.
[0049] [Equation 1]
[0050] ΔY = {(Yield strength of the second sealant layer - Yield strength of the first sealant layer) / Yield strength of the first sealant layer} × 100%
[0051] In the following text, reference will be made to Figure 1 The invention describes in detail the flexible film stack according to the invention and each layer included in the flexible film stack.
[0052] Figure 1 This is a cross-sectional view of the soft film laminate 100 according to the present invention.
[0053] like Figure 1 As shown, the flexible film stack 100 includes a base layer 110, a gas barrier layer 120, and a sealant layer 130. The sealant layer 130 includes a first sealant layer 132 and a second sealant layer 134. In the flexible film stack 100, the base layer 110, the gas barrier layer 120, and the first sealant layer 132 and the second sealant layer 134 can be stacked sequentially.
[0054] (1) Basal layer
[0055] A substrate layer 110 is formed on the outermost layer of the flexible membrane stack 100 to protect the secondary battery from external friction and impact. The substrate layer 110 may be made of a polymer to electrically insulate the electrode assembly from external sources. The substrate layer 110 may comprise one or more materials selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, propylene-based polymers, polyacrylonitrile, polyimide, polyamide, cellulose, aramid, nylon, polyester, poly(p-phenylenebenzobisoxazole), polyarylate, polytetrafluoroethylene, and glass fiber. Of the above materials, the substrate layer 110 is particularly preferably made of polyethylene terephthalate (PET), nylon, or combinations thereof, which have abrasion resistance and heat resistance.
[0056] The substrate 110 can have a single-layer structure made of any material. On the other hand, the substrate 110 can have a composite layer structure in which each layer is composed of two or more materials.
[0057] The substrate layer 110 can have a thickness of 5 μm to 50 μm, specifically 7 μm to 50 μm, and more specifically 7 μm to 40 μm. When the thickness of the substrate layer 110 meets the above range, the pouch film stack can have excellent external insulation properties. Furthermore, since the entire pouch is thin, the energy density of the secondary battery relative to volume can be excellent.
[0058] (2) Gas barrier layer
[0059] A gas barrier layer 120 is stacked between the base layer 110 and the sealant layer 130 to ensure the mechanical strength of the pouch, prevent gas or moisture from entering from the outside of the pouch battery casing, and prevent electrolyte from leaking out from the inside of the pouch battery casing.
[0060] The gas barrier layer 120 can be made of metal, specifically, an aluminum alloy film. When the gas barrier layer is made of an aluminum alloy film, its weight can be reduced while ensuring a certain level or higher mechanical strength. Furthermore, it ensures the supplementation of electrochemical performance and heat dissipation for the electrode assembly and electrolyte. The aluminum alloy film can contain metallic elements other than aluminum, for example, it can contain one or more elements selected from the group consisting of iron (Fe), copper (Cu), chromium (Cr), manganese (Mn), nickel (Ni), magnesium (Mg), silicon (Si), and zinc (Zn).
[0061] Furthermore, the gas barrier layer 120 can have a thickness of 40 μm to 100 μm, specifically 50 μm to 90 μm, and more specifically 55 μm to 85 μm. When the thickness of the gas barrier layer 120 meets the above range, the formability and gas barrier properties during cup formation become excellent.
[0062] (3) Sealant layer
[0063] The sealant layer 130 completely seals the interior of the pouch cell housing from the outside. Here, when the pouch cell housing 310 (containing electrode assemblies) Figure 3 When sealed, the sealing part 350 ( Figure 3 They are thermally bonded together. For this purpose, the sealant layer 130 can be made of a material with excellent thermal bonding strength.
[0064] The sealant layer 130 may have a composite layer structure consisting of two or more materials.
[0065] Specifically, the sealant layer 130 according to the present invention may include a first sealant layer 132 and a second sealant layer 134. In this case, the first sealant layer 132 may be a layer disposed adjacent to the gas barrier layer 120, and the second sealant layer 134 may be a layer disposed on the first sealant layer 132. The first sealant layer 132 and the second sealant layer 134 may be made of materials with different material properties and / or physical properties.
[0066] An interface may exist between the first sealant layer 132 and the second sealant layer 134. This means that the first sealant layer 132 and the second sealant layer 134 are different layers, and also means that these layers can be formed separately.
[0067] According to the present invention, ΔY according to Equation 1 below can be 66% to 120%, specifically 66% to 110%, and more specifically 66% to 100%. Here, ΔY represents the percentage difference between the yield strength of the first sealant layer 132 and the yield strength of the second sealant layer 134 relative to the yield strength of the first sealant layer 132.
[0068] [Equation 1]
[0069] ΔY = {(Yield strength of the second sealant layer - Yield strength of the first sealant layer) / Yield strength of the first sealant layer} × 100%
[0070] When ΔY is greater than 120%, the possibility of interlayer delamination at the interface between the first sealant layer 132 and the second sealant layer 134 increases when external force or gas is generated. Therefore, the soft-pack battery casing 310 ( Figure 3 The sealing durability may deteriorate.
[0071] When ΔY is less than 66%, the extrusion processability of the sealant layer deteriorates during the manufacturing of the plywood laminate. Therefore, low-temperature sealing performance may deteriorate during the sealing process for battery manufacturing after the plywood laminate is manufactured.
[0072] The difference in yield strength between the first sealant layer 132 and the second sealant layer 134 can be less than 8 N / 15 mm, preferably from 1 N / 15 mm to 8 N / 15 mm, and more preferably from 3 N / 15 mm to 7 N / 15 mm. When the difference in yield strength between the first sealant layer 132 and the second sealant layer 134 meets the above range, the possibility of interlayer delamination at the interface between the first sealant layer 134 and the second sealant layer 132 is reduced when external force or gas is generated. Therefore, the soft-pack battery casing 310 can be strengthened. Figure 3 ) sealing durability.
[0073] The yield strength of the first sealant layer 132 can be less than that of the second sealant layer 134. In this case, the first sealant layer 132 has lower fluidity than the second sealant layer 134, and therefore can be easily attached to the gas barrier layer 120 when forming the flexible film laminate 100. Furthermore, the adhesive force at the interface between the gas barrier layer 120 and the first sealant layer 132 can remain high when an external force is applied.
[0074] The first sealant layer 132 and the second sealant layer 134 may comprise materials with different material properties and / or physical properties. For example, the first sealant layer 132 may be made of a material with lower flowability than the second sealant layer 134. In this case, the first sealant layer 132 with low flowability may have a lower yield strength than the second sealant layer 134.
[0075] The thickness ratio of the first sealant layer 132 to the second sealant layer 134 can be from 1:0.3 to 1:3, preferably from 1:0.6 to 1:2.2, and more preferably from 1:1 to 1:1.7. When the thickness ratio of the first sealant layer 132 to the second sealant layer 134 meets the above range, the extrusion processability between the gas barrier layer 120 and the sealant layer 130 can be ensured. At the same time, the fracture strength of the sealing portion can be enhanced.
[0076] In the following text, each of the first sealant layer 132 and the second sealant layer 134 mentioned above will be described in detail.
[0077] 1) First sealant layer
[0078] As described above, the first sealant layer 132 may be a layer arranged adjacent to the gas barrier layer 120.
[0079] The first sealant layer 132 may be made of a polymer material. Specifically, the first sealant layer 132 may be made of one or more materials selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, propylene-based polymers, polyacrylonitrile, polyimide, polyamide, cellulose, aramid, nylon, polyester, poly(p-phenylenebenzobisoxazole), polyarylate, polytetrafluoroethylene, and glass fiber, and preferably may be made of a polyolefin-based resin such as polypropylene (PP) and / or polyethylene (PE). In this case, the polypropylene may comprise cast polypropylene (CPP), acid-modified polypropylene (PPa), or a polypropylene-butene-ethylene terpolymer.
[0080] Particularly preferred is that the first sealant layer 132 is made of acid-modified polypropylene (PPa) to ensure long-term adhesion between the gas barrier layer 120 and the first sealant layer 132. Here, the acid-modified polypropylene may comprise maleic anhydride polypropylene (MAH PP).
[0081] To adjust the yield strength of the first sealant layer 132 to a desired value, additives can be added to the polymer material constituting the first sealant layer 132. For example, at least one of carbon fiber, glass fiber, and aramid fiber can be added as an additive to enhance the yield strength of the first sealant layer 132. For example, the content of the additive by volume can be from about 5% to about 8% based on the total volume of the first sealant layer 132, but is not limited thereto.
[0082] The yield strength of the first sealant layer 132 can be from 7 N / 15 mm to 15 N / 15 mm, preferably from 7.2 N / 15 mm to 9.0 N / 15 mm, and more preferably from 7.5 N / 15 mm to 8.5 N / 15 mm.
[0083] When the yield strength of the first sealant layer 132 is less than 7 N / 15 mm, the difference in yield strength between the first sealant layer 132 and the second sealant layer 134 increases. Therefore, when external force or gas is generated, interlayer delamination occurs at the interface between the first sealant layer 132 and the second sealant layer 134, and the soft-pack battery casing 310 ( Figure 3 The sealing durability may deteriorate.
[0084] When the yield strength of the first sealant layer 132 is greater than 15 N / 15 mm, the extrusion processability of the gas barrier layer 120 and the first sealant layer 132 used for lamination may deteriorate. Furthermore, to increase the yield strength of the first sealant layer 132, the overall strength of the sealant layer 130 needs to be enhanced. Therefore, necking may occur when the first sealant layer 132 and the second sealant layer 134 are extruded. In addition, the difference between the yield strength of the first sealant layer 132 and the yield strength of the gas barrier layer 120 increases, thus the adhesion at the interface between the gas barrier layer 120 and the first sealant layer 132 may deteriorate.
[0085] The first sealant layer 132 may have a thickness of 10 μm to 60 μm, preferably 20 μm to 50 μm, and more preferably 30 μm to 40 μm. When the thickness of the first sealant layer 132 is less than 10 μm, the sealing portion 350 ( Figure 3 The sealing durability and insulation performance of the first sealant layer 132 deteriorate. Furthermore, the yield strength of the first sealant layer 132 decreases, therefore, the sealing portion 350 ( Figure 3 The sealing strength deteriorates. When the thickness of the first sealant layer 132 is greater than 60 μm, the overall thickness of the pouch film stack increases excessively, leading to deterioration in formability. Furthermore, in the pouch battery casing manufactured by forming the pouch film stack, the space 324 for accommodating the electrode assembly ( Figure 3 The energy density of a secondary battery relative to its volume may decrease as a result of the reduction in energy density.
[0086] 2) First sealant layer
[0087] As described above, the second sealant layer 134 may be a layer disposed on the first sealant layer 132.
[0088] The second sealant layer 134 can be made of a material with insulating properties, corrosion resistance, and sealing performance. Specifically, refer to... Figure 3 The second sealant layer 134 directly contacts the electrode assembly 360. Figure 3 ) and / or accommodating space 324 ( Figure 3The electrolyte inside the pouch cell can therefore be made of a material with insulating and corrosion-resistant properties. Furthermore, the second sealant layer 134 must completely seal the interior of the pouch cell to prevent material transfer between the interior and exterior; therefore, it can be made of a material with high sealing performance (e.g., excellent thermal bonding strength).
[0089] To ensure insulation properties, corrosion resistance, and sealing performance, the second sealant layer 134 can be made of a polymer material. Specifically, the second sealant layer 134 can be made of one or more materials selected from the group consisting of polyethylene, polypropylene, polycarbonate, polyethylene terephthalate, polyvinyl chloride, propylene-based polymers, polyacrylonitrile, polyimide, polyamide, cellulose, aramid, nylon, polyester, poly(p-phenylenebenzobisoxazole), polyarylate, polytetrafluoroethylene, and glass fiber. Preferably, the second sealant layer 134 can be made of a polyolefin-based resin such as polypropylene (PP) and / or polyethylene (PE). In this case, the polypropylene can comprise cast polypropylene, acid-modified polypropylene, or a polypropylene-butene-ethylene terpolymer. Here, acid-modified polypropylene can comprise maleic anhydride polypropylene (MAH PP). More preferably, the second sealant layer 134 can be made of cast polypropylene with heat-sealing properties and high tensile strength.
[0090] To adjust the yield strength of the second sealant layer 134 to a desired value, additives can be added to the polymer material constituting the second sealant layer 134. For example, at least one of carbon fiber, glass fiber, and aramid fiber can be added as an additive to enhance the yield strength of the second sealant layer 134.
[0091] The yield strength of the second sealant layer 134 can be from 10 N / 15 mm to 30 N / 15 mm, specifically from 12 N / 15 mm to 17 N / 15 mm, and more specifically from 14 N / 15 mm to 16 N / 15 mm. When the yield strength of the second sealant layer 134 is less than 10 N / 15 mm, fracture may occur along the pair of sealed second sealant layers 134 under external force or gas. Therefore, the soft-pack battery housing 310 ( Figure 3 The sealing durability may deteriorate. When the yield strength of the second sealant layer 134 is greater than 30 N / 15 mm, the difference between the yield strength of the second sealant layer 134 and the yield strength of the first sealant layer 132 increases. Therefore, the risk of delamination at the interface between the first sealant layer 132 and the second sealant layer 134 may increase.
[0092] The second sealant layer 134 may have a thickness of 20 μm to 70 μm, preferably 30 μm to 70 μm, and more preferably 40 μm to 60 μm. When the thickness of the second sealant layer 134 is less than 20 μm, the sealing portion 350 ( Figure 3The sealing durability and insulation properties of the second sealant layer 134 deteriorate. Furthermore, the yield strength of the second sealant layer 134 decreases, therefore, the sealing portion 350 ( Figure 3 The sealing strength deteriorates. When the thickness of the second sealant layer 134 exceeds 70 μm, the overall thickness of the pouch film stack increases excessively, leading to deterioration in formability. Furthermore, in the pouch battery casing manufactured by forming the pouch film stack, the space 324 for accommodating the electrode assembly ( Figure 3 The energy density of a secondary battery relative to its volume may decrease as a result of the reduction in energy density.
[0093] Next, Figure 2 This is a cross-sectional view showing the sealing portion 210 of the soft-pack battery casing according to the present invention.
[0094] like Figure 2 As shown, a battery casing manufactured by forming a laminated soft-film structure can be sealed after the second sealant layers 134 come into contact with and are stacked together. In this case, the seal 210 may include one or more sealant layers 130.
[0095] When pressure is applied to the sealed battery casing due to external forces or the generation of gas, peeling may occur at interfaces with relatively weak adhesive strength. For example, it may occur along the interface between the gas barrier layer 120 and the first sealant layer 132 (e.g., Figure 2 Path A), the interface between the second sealant layers 134 that are thermally bonded to each other (e.g., path A), Figure 2 Path B) and / or the interface between the first sealant layer 132 and the second sealant layer 134 (e.g. Figure 2 The path C) is stripped.
[0096] However, the battery casing manufactured using the soft-film laminate according to the invention exhibits excellent adhesion at all three interfaces, thus demonstrating excellent sealing strength.
[0097] Specifically, in the flexible film laminate according to the present invention, the yield strength of the first sealant layer 132 has a value similar to that of the gas barrier layer 120. Therefore, when an external force is applied, the adhesive force at the interface between the gas barrier layer 120 and the first sealant layer 132 remains high, and peeling between them is suppressed. For example, the peel strength between the gas barrier layer 120 and the first sealant layer 132 can be greater than 23 N / 15 mm, preferably greater than or equal to 23.2 N / 15 mm, and more preferably greater than or equal to 23.5 N / 15 mm. When the peel strength between the gas barrier layer 120 and the first sealant layer 132 meets the above range, peeling at the interface between the gas barrier layer 130 and the first sealant layer 132 can be suppressed.
[0098] Furthermore, the second sealant layer 134 formed on the sealing portion 210 has a high yield strength, thus exhibiting a high restoring force when an external force is applied. Therefore, peeling at the interface between the two thermally bonded second sealant layers 134 can be suppressed.
[0099] Furthermore, the small difference in yield strength between the first sealant layer 132 and the second sealant layer 134 can suppress interlayer delamination at the interface between the first sealant layer 132 and the second sealant layer 134.
[0100] According to an embodiment of the present invention, two soft films are stacked such that their respective second sealant layers 134 are in contact with each other, and then sealed for 2 seconds at 180°C and 0.4 MPa to form a sealing portion 210.
[0101] For example, the breaking strength of the sealing part 210 measured at 25°C can be 100N / 15mm or more, preferably 110N / 15mm or more, and more preferably 120N / 15mm or more.
[0102] In addition, the breaking strength of the sealing part 210 measured at 60°C can be 80N / 15mm or more, preferably 90N / 15mm or more, and more preferably 100N / 15mm or more.
[0103] When the breaking strength of the sealing part 210 at 25°C is less than 100 N / 15 mm, or when the breaking strength of the sealing part 210 at 60°C is less than 80 N / 15 mm, the sealing strength of the sealing part 210 is low. Therefore, the sealed battery casing is prone to leakage due to external force or gas generation.
[0104] The breaking strength of the seal 210 represents the maximum tensile strength measured when the seal breaks. Here, in the sample having the seal 210, the ends of the vertically stacked soft film layers are fastened to the upper / lower clamps of the measuring device UTM, and then pulled vertically at a speed of 5 mm / min. Additionally, "25°C" and "60°C" represent the temperatures when the ends of each of the adjacent soft film layers 100 are pulled vertically.
[0105] Secondary batteries
[0106] Next, the secondary battery according to the present invention will be described.
[0107] Figure 3 This is an exploded assembly diagram of the secondary battery 300 according to the present invention.
[0108] like Figure 3As shown, the secondary battery 300 according to the present invention may include a pouch-type battery casing 310 and an electrode assembly 360 housed within the pouch-type battery casing 310. The electrode assembly 360 can be formed by stacking a positive electrode, a separator, and a negative electrode, and the electrode assembly 360 may include electrode sheets 370, electrode leads 380, and an insulating portion 390. Electrolyte is injected while the electrode assembly 360 is housed inside the pouch-type battery casing 310, and then the sealing portion 350 is used to seal it. Therefore, the secondary battery 300 can be manufactured.
[0109] The electrode assembly 360 can be housed within the pouch cell housing 310. This can be achieved by forming the above... Figure 1 The shown soft-pack film stack 100 is used to manufacture the soft-pack battery casing 310. The detailed configuration and physical properties of the soft-pack film stack 100 are the same as described above, therefore, a detailed description thereof will be omitted.
[0110] To manufacture the pouch-type battery casing 310, the pouch film stack 100 is stretched and elongated using a punch or the like. Thus, a cup portion 322 can be formed, including a pouch-like structure, to accommodate the electrode assembly 360 within a receiving space 324.
[0111] like Figure 3 As shown, the pouch battery housing 310 may include a first housing 320 and a second housing 330. In an embodiment, the first housing 320 may have a cup portion 322 and include a receiving space 324 capable of receiving an electrode assembly 360, and the second housing 330 may cover the receiving space 324 from above to prevent the electrode assembly 360 from being removed from the battery housing 310. The first housing 320 and the second housing 330 may be manufactured such that their respective sides are as follows: Figure 3 The housings are connected to each other as shown (e.g., reference numeral 340), but the embodiments are not limited thereto. These housings may be manufactured in different ways, for example, manufactured separately and separated from each other.
[0112] In another embodiment, when the cup portion 322 is formed in the soft film stack 100, two symmetrical cup portions 322 and 332 can be stretched to be adjacent to each other in a soft film stack 100. In this case, as Figure 3As shown, cup portions 322 and 332 can be formed in the first housing 320 and the second housing 330, respectively. After the electrode assembly 360 is accommodated in the receiving space 324 provided in the cup portion 322 of the first housing 320, the bridging portion 340 formed between the two cup portions 322 and 332 can be folded so that the two cup portions 322 and 332 face each other. In this case, the cup portion 332 of the second housing 330 can accommodate the electrode assembly 360 from above. Therefore, since the two cup portions 322 and 332 accommodate one electrode assembly 360, a thicker electrode assembly 360 can be accommodated compared to when only one cup portion 322 is provided. Furthermore, since one edge of the secondary battery 300 is formed by folding the soft-pack battery housing 310, the number of edges to be sealed when the sealing process is performed later is reduced. Therefore, the processing speed of the secondary battery 300 can be increased, and the number of sealing steps can be reduced.
[0113] The pouch-type battery housing 310 can be sealed with the electrode assembly 360 housed while a portion of the electrode leads 380 (i.e., the terminal portion) is exposed. Specifically, the electrode leads 380 are connected to the electrode plates 370 of the electrode assembly 360, and an insulating portion 390 is formed on a portion of the electrode leads 380. The electrode assembly 360 can then be housed in a receiving space 324 provided in the cup portion 322 of the first housing 320, and the second housing 330 can cover the receiving space 324 from above. Subsequently, an electrolyte can be injected into the receiving space 324, and a sealing portion 350 formed at the edges of the first housing 320 and the second housing 330 can be sealed. The electrolyte moves lithium ions generated by the electrochemical reaction of the electrodes during the charging / discharging of the secondary battery 300, and the electrolyte can contain a non-aqueous organic electrolyte as a mixture of lithium salt and organic solvent, or it can contain a polymer using a polymer electrolyte. Furthermore, the electrolyte can contain a sulfide-based, oxide-based, or polymer-based solid electrolyte, and the solid electrolyte can have sufficient flexibility to be easily deformed by external force.
[0114] Next, an electrode assembly 360 can be formed by alternately stacking electrodes and separators. Specifically, a slurry mixed with electrode active materials, binders, and / or conductive materials is applied to the positive and negative current collectors to create the positive and negative electrodes. These electrodes are then stacked on both sides of the separator to form an electrode assembly 360 with a specific shape. The electrode assembly 360 can be inserted into a pouch cell housing 310 and sealed by the pouch cell housing 310 after electrolyte injection. In embodiments, the type of electrode assembly 360 may include stacked, gel roll, stacked folded, etc., but the embodiments are not limited to these.
[0115] In an embodiment, the electrode assembly 360 may include two types of electrodes, such as a positive electrode and a negative electrode, and a spacer inserted between the electrodes to insulate them from each other. Each of the positive and negative electrodes may have a structure in which an active material slurry is coated onto an electrode current collector in the form of a metal foil or metal mesh comprising aluminum and copper. Typically, the slurry is formed by stirring particulate active material, auxiliary conductor, binder, conductive material, etc., with a solvent added. The solvent can be removed in a subsequent process.
[0116] Electrode sheet 370 is connected to each of the positive and negative electrodes of electrode assembly 360 and protrudes outward from electrode assembly 360, thereby serving as a path for electrons to move between the interior and exterior of electrode assembly 360. The electrode current collector of electrode assembly 360 may include portions coated with electrode active material and ends, i.e., uncoated portions without electrode active material. Electrode sheet 370 can be formed by cutting the uncoated portions, or by connecting individual conductive components to the uncoated portions using methods such as ultrasonic welding. Electrode sheet 370 can be as follows: Figure 3 The electrode assembly 360 is shown to protrude in different directions, but the embodiment is not limited to this. The electrode sheets may protrude in various directions, for example, they may protrude side by side from one side in the same direction.
[0117] Electrode leads 380 can supply power to the outside of the secondary battery 300. Electrode leads 380 can be connected to electrode plates 370 of the electrode assembly 360 by spot welding or the like. At least a portion of the electrode lead 380 can be surrounded by an insulating portion 390. In an embodiment, one end of the electrode lead 380 can be connected to the electrode plate 370, and the other end can protrude outward from the battery housing 310. The electrode lead 380 may include a positive electrode lead 382 and a negative electrode lead 384. One end of the positive electrode lead 382 is connected to the positive electrode plate 372 and extends in the direction of protrusion of the positive electrode plate 372, and one end of the negative electrode lead 384 is connected to the negative electrode plate 374 and extends in the direction of protrusion of the negative electrode plate 374.
[0118] The other ends of both the positive electrode lead 382 and the negative electrode lead 384 can protrude outward from the battery casing 310. Therefore, the electricity generated inside the electrode assembly 360 can be supplied to the outside. Furthermore, since the positive electrode plate 372 and the negative electrode plate 374 protrude in various directions, the positive electrode lead 382 and the negative electrode lead 384 can also extend in various directions. In an embodiment, the positive electrode lead 382 and the negative electrode lead 384 can be made of different materials. That is, the positive electrode lead 382 can have the same aluminum (Al) material as the positive current collector, and the negative electrode lead 384 can have the same copper (Cu) material as the negative current collector or nickel (Ni) coated copper material. A portion of the electrode lead 380 protruding outward from the battery casing 310 serves as a terminal portion and can be electrically connected to an external terminal.
[0119] With the insulating portion 390 confined within the sealing portion 350 (where the first housing 320 and the second housing 330 of the pouch battery housing 310 are thermally fused), the electrode lead 380 can be attached to the battery housing 310. Furthermore, the insulating portion 390 prevents the flow of electricity generated from the electrode assembly 360 through the electrode lead 380 to the battery housing 310, maintaining the airtightness of the battery housing 310. For this purpose, the insulating portion 390 can be made of a non-conductive material that does not allow for good electrical flow. While relatively thin insulating tape that is easily attached to the electrode lead 380 is commonly used as the insulating portion 390, the embodiments are not limited to this. Various components can be used, as long as they are capable of insulating the electrode lead 380.
[0120] The present invention will be described in detail below with reference to specific embodiments. However, the following embodiments are merely examples to aid in understanding the invention and do not limit its scope. It will be apparent to those skilled in the art that various modifications and variations can be made within the scope and concept of this disclosure, and all such modifications and variations are included in the appended claims.
[0121] Examples and Comparative Examples
[0122] Example 1 (Manufacturing of Flexible Sheet Laminates)
[0123] A flexible film laminate was fabricated having a structure of polyethylene terephthalate / nylon / aluminum alloy film / acid-modified polypropylene / cast polypropylene. Here, a polyethylene terephthalate film having a width of 266 mm, a length of 50 m, and a thickness of 12 μm, and a nylon film having a width of 266 mm, a length of 50 m, and a thickness of 25 μm are laminated on one surface of an aluminum alloy film having a width of 266 mm, a length of 50 m, and a thickness of 60 μm. Additionally, acid-modified polypropylene (PPa) having a width of 266 mm, a length of 50 m, and a thickness of 30 μm, and cast polypropylene (CPP) having a width of 266 mm, a length of 50 m, and a thickness of 50 μm are laminated on the other surface of the aluminum alloy film.
[0124] Here, carbon fiber additives that enhance yield strength are added to acid-modified polypropylene at 8 vol%. The acid-modified polypropylene is melted at high temperature and then extruded and stacked on aluminum alloy film and cast polypropylene.
[0125] Here, polyethylene terephthalate and nylon represent the base layer, aluminum alloy film represents the gas barrier layer, acid-modified polypropylene represents the first sealant layer, and cast polypropylene represents the second sealant layer.
[0126] Example 2 (Manufacturing of Flexible Sheet Laminates)
[0127] The soft film laminate was manufactured in the same manner as in Example 1, except that a carbon fiber additive capable of enhancing yield strength was added at 5 vol% to the first sealant layer.
[0128] Comparative Example 1 (Manufacturing of Flexible Sheet Laminates)
[0129] The flexible film laminate was manufactured in the same manner as in Example 1, except that no additives that could enhance yield strength were added to the first sealant layer.
[0130] Comparative Example 2 (Manufacturing of Flexible Sheet Laminates)
[0131] The soft film stack was manufactured in the same manner as in Comparative Example 1, except that the thickness of the first sealant layer was 20 μm.
[0132] Comparative Example 3 (Manufacturing of Flexible Sheet Laminates)
[0133] The soft film laminate was manufactured in the same manner as in Comparative Example 1, except that a carbon fiber additive capable of enhancing yield strength was added at 10 vol% to the first sealant layer.
[0134] The materials and thicknesses of the layers of the soft film laminates manufactured in each of Examples 1-2 and Comparative Examples 1-3 are shown in Table 1 below.
[0135] [Table 1]
[0136]
[0137]
[0138] Experimental Example 1: Measurement of the Yield Strength of the Sealant Layer
[0139] In the examples or comparative examples, the resin constituting each of the first and second sealant layers was extruded in the form of a film, and then the strain-stress curve was measured. Additionally, the yield strength of each of the first and second sealant layers was measured. Furthermore, ΔY was calculated according to Equation 1 using the measured yield strength. The values of yield strength and ΔY are shown in Table 2 below.
[0140] [Equation 1]
[0141] ΔY = {(Yield strength of the second sealant layer - Yield strength of the first sealant layer) / Yield strength of the first sealant layer} × 100%
[0142] Experiment Example 2: Evaluating the peel strength between the gas barrier layer and the sealant layer
[0143] For each of the soft film stacks manufactured in the examples and comparative examples, the peel strength between the gas barrier layer and the sealant layer was measured.
[0144] Specifically, such as Figure 4 As shown, the 180-degree peel strength was measured by peeling the sealant layer from the flexible film laminate manufactured in each of the examples and comparative examples. Additionally, the average strength of flat portions ranging from 5 mm to 25 mm was measured. The results are shown in Table 2 below.
[0145] Figure 4 The state of the peel strength between the gas barrier layer and the sealant layer according to the present invention is shown.
[0146] Experiment Example 3: Evaluate whether interlayer delamination occurs between the first sealant layer and the second sealant layer.
[0147] In Experiment 2, when measuring the peel strength of the gas barrier layer / sealant layer, a visual inspection was conducted to check whether interlayer peeling had occurred between the first sealant layer and the second sealant layer. The measurement results are shown in Table 2 below.
[0148] Experiment Example 4: Evaluation of the fracture strength of the sealing part
[0149] Two soft-film laminates manufactured in each of the examples and comparative examples were stacked such that their respective second sealant layers were in contact with each other. The sealant layers were then sealed for 2 seconds at a sealing strip area of 200 mm × 10 mm, 180°C, and 0.4 MPa to form a seal. The sealed sample was then cut into 15 mm wide pieces. Finally, as... Figure 5 As shown, the ends of the flexible film stack vertically layered in the cut sample were secured to the upper / lower clamps of the measuring device (UTM, Zwick), and then pulled vertically at a speed of 5 mm / min. The maximum tensile strength at which the seal fractured was then measured. The results are shown in Table 2 below.
[0150] Figure 5 The condition of measuring the fracture strength of a seal manufactured using a soft film laminate according to the present invention is shown.
[0151] The results of the measurements based on Experiments 1 to 4 are shown in Table 2 below.
[0152] [Table 2]
[0153]
[0154] According to Experimental Example 1, ΔY was measured to be 82.5% in Example 1, 108.3% in Example 2, 125% in Comparative Example 1, 150% in Comparative Example 2, and 65.1% in Comparative Example 3. That is, in each of Examples 1 and 2, ΔY was measured within the range of 66% to 120%, which is the baseline value of the present invention. On the other hand, in each of Comparative Examples 1 to 3, ΔY was measured to be outside the range of 66% to 120% (the baseline value of the present invention).
[0155] Meanwhile, the difference in yield strength between the first sealant layer and the second sealant layer was measured to be 6.6 N / 15 mm in Example 1, 7.8 N / 15 mm in Example 2, 8.5 N / 15 mm in Comparative Example 1, 9.0 N / 15 mm in Comparative Example 2, and 9.9 N / 15 mm in Comparative Example 3. That is, in each of Examples 1 and 2, the difference in yield strength between the first sealant layer and the second sealant layer was measured to be less than 8 N / 15 mm, which is the baseline value of the present invention. On the other hand, in each of Comparative Examples 1 to 3, the difference in yield strength between the first sealant layer and the second sealant layer was measured to be greater than 8 N / 15 mm (the baseline value of the present invention).
[0156] According to Experimental Example 2, the peel strength between the gas barrier layer and the first sealant layer measured in Example 1 was 24 N / 15 mm, in Example 2 it was 23.6 N / 15 mm, in Comparative Example 1 it was 23 N / 15 mm, in Comparative Example 2 it was 22 N / 15 mm, and in Comparative Example 3 it was 20 N / 15 mm. Therefore, the pouch cell battery casing manufactured by heat-sealing the pouch film stack in each of Examples 1 and 2 can have a superior sealing strength than the pouch cell battery casing manufactured by heat-sealing the pouch film stack in each of Comparative Examples 1 to 3.
[0157] According to Experimental Example 3, no delamination between the first sealant layer and the second sealant layer was observed in the soft-pack film stacks manufactured in each of Examples 1 and 2. On the other hand, delamination between the first sealant layer and the second sealant layer was observed in the soft-pack film stacks manufactured in each of Comparative Examples 1 to 3. Therefore, the soft-pack battery casing manufactured by heat-sealing the soft-pack film stacks in each of Examples 1 and 2 can have superior sealing strength than the soft-pack battery casing manufactured by heat-sealing the soft-pack film stacks in each of Comparative Examples 1 to 3.
[0158] According to Experimental Example 4, the fracture strength of the seal manufactured using the soft-film laminates of each of Examples 1 and 2 was measured to be significantly higher at 25°C and 60°C than that of the seal manufactured using the soft-film laminates of each of Comparative Examples 1 to 3. Therefore, the pouch battery casing manufactured by heat-sealing the soft-film laminates of each of Examples 1 and 2 can have superior sealing strength compared to the pouch battery casing manufactured by heat-sealing the soft-film laminates of each of Comparative Examples 1 to 3.
Claims
1. A flexible film stack, wherein a base layer, a gas barrier layer, and a sealant layer are sequentially stacked in the flexible film stack. in, The sealant layer comprises: First sealant layer; and The second sealant layer is layered on top of the first sealant layer. The first sealant layer is disposed between the gas barrier layer and the second sealant layer. Among them, ΔY obtained according to Equation 1 ranges from 66% to 120%. [Equation 1] ΔY = {(Yield strength of the second sealant layer - Yield strength of the first sealant layer) / Yield strength of the first sealant layer} × 100%.
2. The soft film laminate according to claim 1, wherein, The difference between the yield strength of the first sealant layer and the yield strength of the second sealant layer is less than or equal to 8 N / 15 mm.
3. The soft film laminate according to claim 1, wherein, The yield strength of the first sealant layer is less than the yield strength of the second sealant layer.
4. The soft film laminate according to claim 1, wherein, The yield strength of the first sealant layer is 7 N / 15 mm to 15 N / 15 mm.
5. The soft film laminate according to claim 1, wherein, The yield strength of the second sealant layer is 10 N / 15 mm to 30 N / 15 mm.
6. The soft film laminate according to claim 1, wherein, The thickness ratio of the first sealant layer to the second sealant layer is 1:0.3 to 1:
3.
7. The soft film laminate according to claim 1, wherein, The thickness of the first sealant layer is 10 μm to 60 μm.
8. The soft film laminate according to claim 1, wherein, The thickness of the second sealant layer is 20 μm to 70 μm.
9. The soft film laminate according to claim 1, wherein, The first sealant layer and the second sealant layer comprise polypropylene.
10. The soft-film laminate according to claim 1, wherein, The gas barrier layer contains aluminum.
11. The soft-film laminate according to claim 1, wherein, The peel strength between the gas barrier layer and the first sealant layer is greater than 23 N / 15 mm.
12. The soft-film laminate according to claim 1, wherein, At least one of the first sealant layer and the second sealant layer contains an additive.
13. The soft-film laminate according to claim 12, wherein, The additive contains at least one of carbon fiber, glass fiber, and aramid fiber.
14. The soft-film laminate according to claim 9, wherein, The first sealant layer is made of acid-modified polypropylene, and the second sealant layer is made of cast polypropylene.
15. A secondary battery, comprising: A pouch battery casing, wherein the pouch battery casing is manufactured by forming a pouch film laminate according to any one of claims 1 to 14; as well as The electrode assembly is housed inside the pouch-type battery casing.
16. The secondary battery according to claim 15, wherein, The soft-pack battery casing includes a sealing portion, and the sealing portion has a breaking strength of 100N / 15mm measured at 25°C.
17. The secondary battery according to claim 15, wherein, The soft-pack battery casing includes a sealing portion, and the sealing portion has a breaking strength of 80 N / 15 mm as measured at 60°C.
18. The secondary battery according to claim 16 or 17, wherein, The two soft films are stacked in such a way that their respective second sealant layers are in contact with each other, and then sealed for 2 seconds at 180°C and 0.4 MPa to form the sealing part.
Citation Information
Patent Citations
Method for determining purpose of building in a user-participating recognition platform using aritificial intelligence and apparatus therefore
KR1020210131121A
Film pack battery
CN104412407A
Packaging material for batteries, method for producing same, and battery
CN107408645A